2013
DOI: 10.1155/2013/296597
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Roux-en-Y Gastric Bypass in a Publically Funded Obesity Program

Abstract: Background. There is limited literature assessing the outcomes of bariatric surgery in a publically funded, North American, multidisciplinary bariatric program. Our objective was to assess outcomes of roux-en-Y gastric bypass (RYGB) in a publically funded bariatric program through a retrospective review of patient records. Methods. 293 patients spent a median of 13 months attending a multidisciplinary obesity clinic prior to undergoing laparoscopic RYGB surgery. The hospital was a Canadian, publically funded, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Anastomotic or staple line leaks are a major complication of bariatric surgery and occur in up to 4.8% of RYGB and 2.4% in LSG [14][15][16]. These leaks are characterized by a discontinuity at the surgical line anastomosis resulting in a spillage of luminal content into the peritoneum [17].…”
Section: Anastomotic Leaksmentioning
confidence: 99%
“…Anastomotic or staple line leaks are a major complication of bariatric surgery and occur in up to 4.8% of RYGB and 2.4% in LSG [14][15][16]. These leaks are characterized by a discontinuity at the surgical line anastomosis resulting in a spillage of luminal content into the peritoneum [17].…”
Section: Anastomotic Leaksmentioning
confidence: 99%
“…Reviews of bariatric surgery in Canada have suggested the procedure is under-accessed and under-utilized as an effective strategy to manage patient weight and correspondingly, prevalence of obesity-related comorbidities ( 5 ). Numerous reports have acknowledged the issue of limited bariatric service capacity and its impact on patient health, including additional costs and mortality while awaiting surgery ( 6 – 10 ). After referral for surgery, some patients in Canada do not complete the program for various reasons including dropout or seeking surgery elsewhere.…”
Section: Introductionmentioning
confidence: 99%